Levetiracetam Induced Behavioural Changes in an Adult Female Patient: A Case Report - Virani, Hemangi Amrutbhai; Dabhi, Hetal Kantilal; Pargi, Piyushkumar Mansinh (Current Drug Safety, 2025)
Background Levetiracetam, a relatively recent addition to antiepileptic medications, is known for its broad-spectrum efficacy in treating partial and generalized tonic-clonic seizures in individuals of all age groups. Despite its favourable tolerability profile, rare instances of psychiatric side effects have been reported. This case study presents a rare occurrence of significant behavioural changes attributed to levetiracetam in a young female patient. Case History A 40-year-old woman with a long-standing history of epilepsy, well-managed with medication, presented with abrupt-onset behavioural changes, including irritability, aggression, crying spells, insomnia, increased talkativeness, and screaming. Notably, these behavioural changes were unrelated to seizure activity and emerged without precedent. A dose reduction of levetiracetam was also attempted, which proved ineffective in mitigating her symptoms. Conclusion Consequently, the drug was discontinued, resulting in the resolution of the behavioural symptoms. This case highlights levetiracetam as the likely causative factor behind the observed significant behavioural changes.
Keywords: Levetiracetam